Synthesis, characterization, and bioactivities of dithiocarbazate-Schiff base ligands and their metal complexes - Low, May Lee (2014)
There is an urgent need to discover new drugs with novel mechanisms of action,higher activity and improved selectivity to address the severe challenge of multidrug resistance in treating bacterial infections and cancer. In view of this, Schiff bases derived from S-substituted dithiocarbazate and their corresponding metal complexes with a plethora of potentially exciting biological activities and coordination chemistry are attractive candidates for consideration. Macroacyclic and open chain metal complexes with their respective tetradentate and bidentate nitrogen-sulphur (NS) Schiff base ligands derived from the condensation of S-benzyldithiocarbazate (SBDTC) and S-methyldithiocarbazate (SMDTC) with 2,5-hexanedione, methyl levulinate, levulinic acid, 4-carboxybenzaldehyde and 3- acetylcoumarin have been prepared. The compounds were fully characterized with various physico-chemical and spectroscopic methods. A total of 11 crystal structures were determined throughout this work. In order to provide more insight into the behaviour of the complexes in solution, electron paramagnetic resonance (EPR) and cyclic voltammetry (CV) experiments were performed. Conjugation of the most promising antimicrobial compound (Schiff base of SBDTC with 4-carboxybenzaldehyde) to various vectors (polyarginine, oligoethylene glycol (OEG) and phenylalanine-arginine-β-napthylamide (PAβN)) was achieved using either standard solid phase or solution synthetic methodologies to prepare improved therapeutic agents. Among the conjugates, the nonaarginine (R9) derivatives showed the most encouraging synergistic effect upon conjugation and complexation to copper ion with enhanced water solubility, bacteria cell membrane permeability and bioactivity. The Cu(II) R9 derivatives possess remarkable antibacterial activity against a wide spectrum of bacteria and in particular, highly efficacious against Staphylococcus aureus with MIC values up to 1-0.5 μM when tested against nine strains of Gram-positive and Gram-negative bacteria. This appears to be the pioneer study to show that the conjugation of polyarginine to dithiocarbazate compounds can greatly influence their therapeutic potential. Cytotoxic assay was also carried out for selected non-conjugated compounds. All the selected Cu(II) complexes assayed against breast cancer cells lines (MCF-7 and MDA-MB-231) exhibited good cytotoxicity with lower IC50 values (0.71-8.31 μM) in comparison to their respective ligands. This work highlights the relevance of metal complexation strategy to stabilize the ligands and improve their bioactivity. The structure-activity relationships of the compounds are discussed.